Category «misdemeanour» in criminal and administrative liability - Yushchyk, Olena; Krainii, Pavlo (Universitatea „Ovidius” Constanţa, 2023)
The article deals with the problem of introducing a criminal offense into national legislation. The authors analyzes the category of "misdemeanor" in criminal and administrative liability. Adaptation of Ukrainian legislation to EU legislation, Ukraine's aspiration to become a democratic state governed by the rule of law requires particular adjustments in the legal system and, accordingly, administrative and criminal law as its constituent. It is of fundamental importance to implement reforming of administrative and criminal legislation on the basis of principles of the Constitution of Ukraine with a comprehensive approach to reforming other areas of legislation (for instance, civil, labour, financial, etc.). It is necessary to forecast dynamics of administrative and criminal law development, interconnected with the gradual changes in the advancement of society.
Keywords: crime, criminal misdemeanor, administrative offense, classification of crimes, Concept of Criminal Justice Reform